Recurrent appendicitis of vermiform appendix after a prior appendectomy: A case report and review of the literature. (May 2022) - Almas, Talal; Nagarajan, Vikneswaran Raj; Ahmed, Danyal; Ullah, Muneeb; Ashary, Mohammed Ali; Oruk, Mert; Khan, Arsalan; Amin, Kiran; Malik, Uzair; Ramjohn, Joshua; Huang, Helen; Rifai, Ali; et al.
Abstract: Introduction: Acute appendicitis is one of the leading causes of acute abdominal pain and surgical emergency. Stump appendicitis is a known complication of appendectomy whereby a retained appendiceal tip serves as a nidus for recurrent bouts of inflammation. Nevertheless, full-blown appendicitis of the vermiform appendix after a prior appendectomy remains a diagnostic conundrum. Case presentation: A 45-year-old woman presented with a six-month history of right iliac fossa pain. Pertinently, she had undergone a prior open appendectomy twelve years ago. Further investigative workup revealed full-blown appendicitis, which was not attributable to a retained appendiceal stump. A subsequent laparoscopic appendectomy was performed, and the resultant specimen was sent for further evaluation, confirming the diagnosis of recurrent appendicitis. Clinical discussion: Acute appendicitis is one of the most common life-threatening abdominal surgical emergencies worldwide, with 300000 appendectomies performed annually in the United States alone. Stump and chronic appendicitis are two separate and exceedingly rare clinical entities that may present simultaneously and develop serious complications unless promptly recognized and appropriately managed. The present paper prompts the clinicians to distinguish amongst the two at the initial surgery in order to thwart further exacerbations. Conclusion: While stump appendicitis is a rare but well-characterized complication of a prior appendectomy, full-blown appendicitis of vermiform appendix remains elusive. It is therefore imperative to distinguish between a duplicated and a recurrent appendix at the initial operative procedure to facilitate optimal patient management. Highlights: Recurrent appendicitis in the aftermath of a prior appendectomy remains an under-recognized cause of acute right iliac fossa pain. While stump appendicitis is a well-characterised complication of laparoscopic or open appendectomy, full-blown appendicitis of a regrown appendix continues to be an elusive clinicopathological phenomena. It remains crucial to distinguish between a duplicated appendix and a regrown appendix in the wake of an appendectomy to better inform the debate on its optimal medical or surgical management. Correctly identifying the appendiceal base during surgery and ensuring a post-resection stump length of no more than 3 mm can preclude the possibility of stump appendicitis. Surgeons should be cognizant of this anatomical aberration and should therefore exclude appendiceal duplication at the time of the index surgery.